2020
DOI: 10.1093/infdis/jiaa678
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Viability as a Superior Measure of Antimalarial Drug Activity in Humans

Abstract: Background Artemisinin derivatives are the leading class of antimalarial drugs due to their rapid onset of action and rapid clearance of circulating parasites. The parasite clearance (PC) half-life measures the rate of loss of parasites from blood after treatment, and this is currently used to assess antimalarial activity of novel agents and to monitor resistance. However, a number of recent studies have challenged the use of PC to measure drug activity, arguing that many circulating parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Apart from ethical concerns regarding the use of animals, and 4 the considerable amount of time and cost required by these in vivo studies, only a small number of doses can be tested, hence preventing the exploration of the full combined response surface of the antimalarial effects. Another important limitation of these studies is the uncertainty of parasite killing following drug treatment since conventional methods cannot reliably distinguish viable from dying or dead parasites (9,10). Indeed, the parasite clearance rate (viable versus dead parasites), measured immediately after treatment, may differ between in vivo models owing different clearance mechanisms of dead parasites from the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from ethical concerns regarding the use of animals, and 4 the considerable amount of time and cost required by these in vivo studies, only a small number of doses can be tested, hence preventing the exploration of the full combined response surface of the antimalarial effects. Another important limitation of these studies is the uncertainty of parasite killing following drug treatment since conventional methods cannot reliably distinguish viable from dying or dead parasites (9,10). Indeed, the parasite clearance rate (viable versus dead parasites), measured immediately after treatment, may differ between in vivo models owing different clearance mechanisms of dead parasites from the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor —In a study of 10 Plasmodium falciparum –infected volunteers with submicroscopic parasitemias given a single 200-mg dose of artesunate, Rebelo et al [ 1 ] reported a substantial difference in the ex vivo growth of sequentially sampled circulating ring-stage [ 2 ] parasites comparing infections with artemisinin-sensitive (Pfkelch wild-type) and artemisinin-resistant (Pfkelch R539T) parasites. In the 5 artemisinin-sensitive infections, they derived an estimated ex vivo mean parasite “viability” reduction half-life of 0.75 hour, considerably shorter than the corresponding 3.2-hour in vivo mean parasite clearance half-life estimate.…”
mentioning
confidence: 99%
“…The serial quantitative polymerase chain reaction derived parasitemia profiles shown by Rebelo et al [ 1 ], fig 3 strongly suggest continued input into the circulation from ongoing schizogony [ 2 , 8 ]. This explains why parasite densities in blood do not fall for approximately 8 hours.…”
mentioning
confidence: 99%
See 2 more Smart Citations